Double minute chromosomes harboring MDM2 amplification in a pediatric atypical lipomatous tumor. Issue 9 (13th April 2019) - Dadone‐Montaudié, Bérengère; Burel‐Vandenbos, Fanny; Soler, Christine; Rosello, Olivier; Boyer, Corinne; Fabas, Thibault; Bianchini, Laurence; Pedeutour, Florence
Abstract: Adipocytic tumors are rare in children and are mostly benign. Less than 25 cases of pediatric well‐differentiated liposarcoma (WDLPS), atypical lipomatous tumors (ALT), and dedifferentiated liposarcoma (DDLPS) have been reported. Among them, only three cases were genetically analyzed. We describe the genetic features of a rapidly growing adipose tumor that occurred in the thigh of a 7‐year‐old girl. Histologically, it was composed of mature adipocytic cells with a few atypia. Molecular analysis showed high‐level amplification of the 12q13‐21 region including MDM2 among 64 amplified genes. MDM2 amplification is a diagnostic hallmark of ALT/WDLPS/DDLPS. In adult cases, it is typically located in ring or giant marker chromosomes. In the present case, extra‐copies of MDM2 were located on double minute chromosomes (dmin). This raised the hypothesis of dmin being precursors of adult's rings and giant markers and may provide indications for a better understanding of the mechanisms of adipose tumor oncogenesis.